2023
DOI: 10.1093/alcalc/agad055
|View full text |Cite
|
Sign up to set email alerts
|

The adolescent and young adult microbiome and its association with substance use: a scoping review

Brittney D Browning,
Anna E Kirkland,
Rejoyce Green
et al.

Abstract: Aims The microbiome is a critical factor in health throughout human development. The aims of this scoping review are to (i) elucidate the differences between the youth (post-natal day 21–65 for rodents, 2–7 years for non-human primates, and 10–25 years for humans) microbiome with other life stages and (ii) identify youth-specific microbial changes associated with substance use. Methods Peer-reviewed studies published up to Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 109 publications
0
1
0
Order By: Relevance
“…However, the same methodology could be expanded to adults. Studies suggest that the gut microbiome can be significantly different between children and adults [36,37]. Therefore, further studies would need to be carried out to understand if the same markers can be observed in adults as in children, or to identify the ones more relevant to specific age groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, the same methodology could be expanded to adults. Studies suggest that the gut microbiome can be significantly different between children and adults [36,37]. Therefore, further studies would need to be carried out to understand if the same markers can be observed in adults as in children, or to identify the ones more relevant to specific age groups.…”
Section: Discussionmentioning
confidence: 99%
“…The brain undergoes significant structural and functional changes (e.g., changes in brain structural volume, cortical thickness, and myelination) and does not finish maturing until early adulthood (Casey et al., 2008). Similarly, both the gut and oral microbiomes mature during adolescence, experiencing alterations in the number of bacteria and their distribution (diversity) and the specific types of bacteria and their abundances (composition) (Browning et al., 2024; McVey Neufeld et al., 2016). Importantly, key neurodevelopmental trajectories overlap with a timeframe of peak plasticity in the gut and oral microbiomes (Cowan et al., 2020; Stahringer et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that germ free mice, mice raised in sterile conditions with no microbiome, have deficits in many areas of brain development and function, including effects on myelination, neurotransmission, synaptic plasticity, microglia function, neurogenesis, dendritic growth, and blood–brain barrier permeability (Cryan et al., 2019). In addition, the adolescent gut and oral microbiomes are particularly sensitive to environmental exposures, including alcohol and other substances (Browning et al., 2024). This suggests adolescence may be a crucial period of development where perturbations to the microbiome can lead to long‐term neural changes that could increase vulnerability for the development of AUD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation